Urinary Erythropoietic Factor in Aplastic Anemia - Rodríguez Tapia, Nicanor U. (1965)
Carnot and Deflandre , in 1906 , were the first researchers who dealt with the study of humoral factor , which they called haemopoietin later experimental work was done on animals by bleeding and falling barometric pressure , suggesting that the stimulus would occur from these causes. Later Reissman ( 1) , in their experience is that humoral mechanism for hypoxia stimulates erythropoiesis . Stohlman ( 2) , and others , in patients with ductus arteriosus , did a study on saturation and oxygen tension , supporting the mechanism mentioned above. In 1953 , Erslev ( 3) plasma transfused to normal recipients anemic getting reticulocytosis ( 6 to 10 % ) and a significant increase in hematocrit . Van Dyke (8 ) studied this factor in several clinical cases of anemia, finding positive in some cas.os of aplastic anemia. These facts suggested us to perform this study on erythropoietin, which was first made ​​in aplastic anemia in our country, with the {in contributing to a better understanding of this problem, which is in the early stages of their study. The problem of erythropoietin and some pathological cases equipment has been studied in six students of the Faculty of Medicine at San Fernando , at the Institute of Andean Biology , led by Dr. César Reynafarje , ; when they had unrequited deal on urinary erythropoietin in Aplastic Anemia .